Un problema de difusión para una ecuación del tipo Ni-Serrin con término de convección - Cabanillas Lapa, Eugenio (2025)
The purpose of this article is to study the existence of weak solutions for a class of nonlinear nonlocal Dirichlet parabolic problem with p(x)-Laplacian-like operators with a convection term. We apply degree theory to operators of the type T + S + C, where T is maximal monotone, S is bounded pseudomonotone, and C is compact with D(T) ⊆ D(C) and satisfies a sublinearity condition, to get our result within the context of Sobolev spaces with variable exponents.